Miocene extensional tectonics explain ancient patterns of diversification among turret‐building tarantulas (Aphonopelma mojave group) in the Mojave and Sonoran deserts. (4th March 2015) - Graham, Matthew R.; Hendrixson, Brent E.; Hamilton, Chris A.; Bond, Jason E.; McGeoch, Melodie
Abstract Aim Phylogeographical studies in the Mojave and Sonoran deserts often find genetic discontinuities that pre‐date the Pleistocene. A recent synthesis of phylogeographical data, called the Mojave Assembly Model, provides a hypothesis for the historical assembly of these desert biotas but does not adequately capture the complexity of pre‐Pleistocene vicariance events. We tested this model and assessed pre‐Pleistocene divergences by exploring the phylogeography of the Aphonopelma mojave group, which is composed of turret‐building tarantula species from the Mojave and Sonoran deserts. Location Mojave and Sonoran deserts, south‐western USA. Methods We augmented the sampling from a previous study by sequencing mitochondrial DNA (COI) from new material of the A. mojave group. We used phylogenetic and network analyses to identify clades and a molecular clock and lineages‐through‐time plots (LTT plots) to explore the timing and tempo of diversification. We tested for demographic expansion using neutrality tests and mismatch distributions. Species distribution models (SDMs) were constructed to compare current suitable habitat to that at the Last Glacial Maximum (LGM). Results Phylogenetic, network and molecular‐clock analyses identified six major clades that probably diverged during the late Miocene. The rate of diversification appears to have slowed during the Pliocene. Most clades exhibit signals of recent demographic expansion. SDMs predicted that suitable habitat shifted south and to lower elevations during the LGM. Main conclusions Phylogeographical analyses suggest that the A. mojave group experienced a burst of diversification in the late Miocene, followed by population expansions during the Pleistocene. Six major clades with origins in the late Miocene cannot be adequately explained by the Mojave Assembly Model. We propose the novel hypothesis that Miocene extensional tectonics caused populations to diverge in allopatry by producing low‐elevation habitat barriers. Geological models, such as kinematic reconstructions, provide an ideal but underutilized framework for testing biogeographical hypotheses in these deserts and the wider Basin and Range Province.